An Automatic Design Flow for Data Parallel and Pipelined Signal Processing Applications on Embedded Multiprocessor with NoC: Application to Cryptography. (2nd November 2009) - Li, Xinyu; Hammami, Omar
Abstract : Embedded system design is increasingly based on single chip multiprocessors because of the high performance and flexibility requirements. Embedded multiprocessors on FPGA provide the additional flexibility by allowing customization through addition of hardware accelerators on FPGA when parallel software implementation does not provide the expected performance. And the overall multiprocessor architecture is still kept for additional applications. This provides a transition to software only parallel implementation while avoiding pure hardware implementation. An automatic design flow is proposed well suited for data flow signal processing exhibiting both pipelining and data parallel mode of execution. Fork-Join model-based software parallelization is explored to find out the best parallelization configuration. C-based synthesis coprocessor is added to improve performance with more hardware resource usage. The Triple Data Encryption Standard (TDES) cryptographic algorithm on a 48-PE single-chip distributed memory multiprocessor is selected as an application example of the flow.